PENGARUH SOFTWARE TRACKER PADA PEMBELAJARAN KOEFISIEN RESTITUSI BERBASIS INKUIRI TERBIMBING TERHADAP KEMAMPUAN MULTIPLE REPRESENTATIONS SISWA - Oktaviani, Yeni; Wahyudi, Ismu; Abdurrahman, Abdurrahman (Kappa Journal, 2020)
The effect of software tracker on learning coefficient restitution based inquiry guided on ability of multiple representations. Software tracker in learning the restitution coefficient can help to track the motion of objects at a more precise and accurate time, helping students get the track of objects that based on these tracks students can be guided to find concepts or equations of object motion. This study aims to describe how the influence of usingatrackeronguided inquiry based restitution coefficient learning on the ability of multiple representations ( MR ). The population of this research is all grade X students of Muhammadiyah 1 Purbolinggo Senior High School. The sample of thisresearch is students of gradeX MIPA 2 Muhammadiyah 1Purbolinggo Senior High School. The research design used is the One Group Pretest-Post testDesign.Learningis done by practicing guided inquiry of restitutioncoefficien practicum activities,then processing the experimental data byanalyzing the experimental video using a software of tracker. Ability MR of students is obtained from the learning process in the formofpretestand posttest. Analisis data is done using Paired Sample T-Test. Based on the results of the study obtained an average score of ability MR has increasedby 58,64 % with an average N-Gain in the medium category (0,68 ). These results indicate that learning by using a tracker can improve ability MR with good with a significance value of 0.00.